PENILAIAN RISIKO DAN PENENTUAN SISA UMUR TERHADAP PIPA GAS TEE 24" DI PT.X DENGAN MENGGUNAKAN METODE RISK BASED INSPECTION - Gunawan Dwi Haryadi; Agus Suprihanto; Auda Sephanya; Ismoyo Haryanto (ROTOR, 2019)
Risk Based Inspection (RBI) of 24” oil pipe according API 581 has been conducted. The analysis shows that the piping system has medium risk. The remaining life is between 6-7 years. Because piping failure is due thinning, the next inspection using NDT is suggested not more half of the remaining life.